Assessing surgeon stress when operating using heart rate variability and the State Trait Anxiety Inventory: will surgery be the death of us?. (April 2015) - Jones, K. I.; Amawi, F.; Bhalla, A.; Peacock, O.; Williams, J. P.; Lund, J. N.
Abstract: Aim: Performance in the operating room is affected by a combination of individual, patient and environmental factors amongst others. Stress has a potential negative impact on performance with the quality of surgical practice and patient safety being affected as a result. In order to appreciate the level of stress encountered during surgical procedures both objective and subjective methods can be used. This study reports the use of a combined objective (physiological) and subjective (psychological) method for evaluating stress experienced by the operating surgeon. Method: Six consultant colorectal surgeons were evaluated performing eighteen anterior resections. Heart rate was recorded using a wireless chest strap at eight pre‐determined operative steps. Heart Rate Variability indices were calculated offline using computerized software. Surgeon reported stress was collected using the State Trait Anxiety Inventory, a validated clinical stress scale. Results: A significant increase in stress was demonstrated in all surgeons whilst operating as indicated by sympathetic tone (control: 4.02 ± 2.28 vs operative: 11.42 ± 4.63; P < 0.0001). Peaks in stress according to operative step were comparable across procedures and surgeons. There was a significant positive correlation with subjective reporting of stress across procedures ( r = 0.766; P = 0.0005). Conclusion: This study demonstrates a significant increase in sympathetic tone in consultant surgeons measured using heart rate variability during elective colorectal resections. A significant correlation can be demonstrated between HRV measurements and perceived stress using the State Trait Anxiety Inventory. A combined approach to assessing operative stress is required to evaluate any effect on performance and outcomes.